Nerve Growth Factor Compromise in Down Syndrome - Sonia Do Carmo (Frontiers in Aging Neuroscience, 2021)
The basal forebrain cholinergic system relies on trophic support by nerve growth factor (NGF) to maintain its phenotype and function. In Alzheimer’s disease (AD), basal forebrain cholinergic neurons (BFCNs) undergo progressive atrophy, suggesting a deficit in NGF trophic support. Within the central nervous system, NGF maturation and degradation are tightly regulated by an activity-dependent metabolic cascade. Here, we present a brief overview of the characteristics of Alzheimer’s pathology in Down syndrome (DS) with an emphasis on this NGF metabolic pathway’s disruption during the evolving Alzheimer’s pathology. Such NGF dysmetabolism is well-established in Alzheimer’s brains with advanced pathology and has been observed in mild cognitive impairment (MCI) and non-demented individuals with elevated brain amyloid levels. As individuals with DS inexorably develop AD, we then review findings that support the existence of a similar NGF dysmetabolism in DS coinciding with atrophy of the basal forebrain cholinergic system. Lastly, we discuss the potential of NGF-related biomarkers as indicators of an evolving Alzheimer’s pathology in DS.